A hepatic GAbp-AMPK axis links inflammatory signaling to systemic vascular damage - Niopek, Katharina; Sakurai, Minako; Feuchter, Yvonne; Leuchs, Barbara; Niopek, Dominik; Brune, Maik; Sticht, Carsten; Gretz, Norbert; Hammes, Hans-Peter; Nawroth, Peter Paul; Fleming, Thomas; Herzig, Stephan; et al. (Cell reports, 2017)
Increased pro-inflammatory signaling is a hallmark of metabolic dysfunction in obesity and diabetes. Although both inflammatory and energy substrate handling processes represent critical layers of metabolic control, their molecular integration sites remain largely unknown. Here, we identify the heterodimerization interface between the α and β subunits of transcription factor GA-binding protein (GAbp) as a negative target of tumor necrosis factor alpha (TNF-α) signaling. TNF-α prevented GAbpα and β complex formation via reactive oxygen species (ROS), leading to the non-energy-dependent transcriptional inactivation of AMP-activated kinase (AMPK) β1, which was identified as a direct hepatic GAbp target. Impairment of AMPKβ1, in turn, elevated downstream cellular cholesterol biosynthesis, and hepatocyte-specific ablation of GAbpα induced systemic hypercholesterolemia and early macro-vascular lesion formation in mice. As GAbpα and AMPKβ1 levels were also found to correlate in obese human patients, the ROS-GAbp-AMPK pathway may represent a key component of a hepato-vascular axis in diabetic long-term complications.